Differential Diagnosis in the Management of CPI Immunotoxicity: Case Series of Etiologies not to Miss. (5th December 2022) - Gregory, Timothy; Tummala, Sudhakar
Abstract : Objective: To present on treatable conditions arising with exposure to checkpoint inhibiting immunotherapy for malignancy. Each case was diagnostically obscured by presumed immunotoxicity. Background: Neurological immune-related adverse events (n-irAEs) are rising in incidence with adoption of checkpoint inhibitors (CPIs) for many cancers. 1-3% of patients treated with CPIs experience severe n-irAEs with potential for persistent functional disability or mortality. Diagnosis can be challenging for immunologically vulnerable patients with frequently multifactorial problems from their cancer and potential infectious, metabolic, and iatrogenic complications. Design/Methods: Three informative cases from a single institution were analyzed. Results: 1. An 80-year old woman with metastatic melanoma and recent treatment with ipilimumab+pembrolizumab developed acute leg weakness. Given her EMG and CSF findings, she began treatment for suspected CPI-induced atypical GBS and myositis. Concomitantly she was found to have B12 and folate deficiencies, then gradually improved to baseline with vitamin repletion, steroids, and plasma exchange. 2. A 27-year old woman with metastatic melanoma and recent treatment with ipilimumab+nivolumab developed autoimmune hepatitis and intractable vomiting. Three weeks after she began dabrafenib and trametinib, she developed confusion, diplopia, and ataxia along with weakness and areflexia. She was treated for possible GBS, but was concurrently found to have thiamine deficiency with sequela of Wernicke's encephalopathy on MRI Brain. Her confusion improved with thiamine supplementation but had persistent weakness. 3. A 57-year old woman with lung adenocarcinoma who had progressed on durvalumab began pembrolizumab. Two weeks later, she developed fevers, rash, and lethargy. She was treated supportively but continued to worsen until neurological workup revealed limbic hyperintensities on MRI Brain and CSF pleocytosis with +HSV1. She had minor clinical improvement with acyclovir but remained cognitively debilitated. Conclusions: Given frequently complex clinical circumstances when working up n-irAEs, a systematic approach and a broad differential must be utilized for this important intersection of cancer neurology and immunology.